EFFECTIVENESS OF KINESIOLOGICAL TAPE IN MYOFASCIAL PAIN SYNDROME OF GASTROCNEMIUS MUSCLE: Kinesiological Tape Effectiveness in Myofascial Pain Syndrome - Gill, Riffat Asghar; Bashir, Muhammad Salman; Khalid, Kehkshan; Anwar, Naveed (Pakistan Armed Forces Medical Journal, 2021)
Objective: To see the effectiveness of kinesiological tape in myofascial pain syndrome of gastrocnemius muscle for the early recovery after injury and thus increase functional outcome.Study Design: Quasi-experimental study.Place and Duration of Study: National cricket academy Lahore and Sports and Spine Professional’s Clinic, Defense Phase-IV Lahore Pakistan, from Aug 2017 to Oct 2017.Methodology: Consecutive sampling technique was used to enrol the patients of myofascial pain syndrome based on the predefined inclusion and exclusion criteria. Patients were selected and the kinesiological tape was applied thrice a week for two consecutive weeks. the patient was then re-evaluated after every two days of previous kinesiological tape application in terms of the visual Analogue Scale. Results: It was observed that kinesiological tape had a significant effect on pain reduction of the myofascial pain syndrome of the gastrocnemius muscle (p